Slovenia: Interest group developments in a postsocialist‐liberal democracy. Issue 2 (25th January 2019) - Novak, Meta; Fink‐Hafner, Danica
Abstract : Slovenia has a rich tradition of associations and interest group activity dating back to the 19th century. To some extent, the development of the group system was stymied by the 60 years of authoritarian rule from the early 1930s to the late 1980s. However, the resilience of this tradition is evident in major developments in group activity since the return to democracy. In addition to influences from the past, including a neocorporatist tradition, is the impact of Slovenia's process of integration into the European Union. This article considers the extent to which the modern nature of the interest group system is both constrained by hangovers from the past but enhances by European integration, both of which have affected the development of Slovenia's majoritarian democracy.